Aldose reductase (AKR1B) deficiency promotes phagocytosis in bone marrow derived mouse macrophages. (1st March 2017) - Singh, Mahavir; Kapoor, Aniruddh; McCracken, James; Hill, Bradford; Bhatnagar, Aruni
Abstract: Macrophages are critical drivers of the immune response during infection and inflammation. The pathogenesis of several inflammatory conditions, such as diabetes, cancer and sepsis has been linked with aldose reductase (AR), a member of the aldo-keto reductase (AKR) superfamily. However, the role of AR in the early stages of innate immunity such as phagocytosis remains unclear. In this study, we examined the role of AR in regulating the growth and the phagocytic activity of bone marrow-derived mouse macrophages (BMMs) from AR-null and wild-type (WT) mice. We found that macrophages derived from AR-null mice were larger in size and had a slower growth rate than those derived from WT mice. The AR-null macrophages also displayed higher basal, and lipopolysaccharide (LPS) stimulated phagocytic activity than WT macrophages. Moreover, absence of AR led to a marked increase in cellular levels of both ATP and NADPH. These data suggest that metabolic pathways involving AR suppress macrophage energy production, and that inhibition of AR could induce a favorable metabolic state that promotes macrophage phagocytosis. Hence, modulation of macrophage metabolism by inhibition of AR might represent a novel strategy to modulate host defense responses and to modify metabolism to promote macrophage hypertrophy and phagocytosis under inflammatory conditions. Highlights: AR deficient macrophages divide slowly, have more ATP and NADPH/NADP. AR is an inhibitor of phagocytosis in macrophages. AR deficient macrophages are larger in size.